2011
DOI: 10.1161/circresaha.110.237420
|View full text |Cite
|
Sign up to set email alerts
|

Microparticles From Human Atherosclerotic Plaques Promote Endothelial ICAM-1–Dependent Monocyte Adhesion and Transendothelial Migration

Abstract: Rationale and Objective: Membrane-shed submicron microparticles (MPs) released following cell activation or apoptosis accumulate in atherosclerotic plaques, where they stimulate endothelial proliferation and neovessel formation. The aim of the study was to assess whether or not MPs isolated from human atherosclerotic plaques contribute to increased endothelial adhesion molecules expression and monocyte recruitment. Method and Results:Human umbilical vein and coronary artery endothelial cells were exposed to MP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
199
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 228 publications
(222 citation statements)
references
References 37 publications
8
199
0
3
Order By: Relevance
“…Microparticles (MPs) are 0.1-1-μm membrane vesicles that are released into the extracellular space following cell activation or apoptosis 33) . Several cardiovascular risk factors, such as oxidative stress and elevated levels of lipoproteins and cytokines, increase the release of MPs from vascular/circulation cells 34,35) , and a large number of studies have proposed that MPs may contribute to atherosclerotic plaque development and thrombus formation/progression [35][36][37][38] . In fact, circulating MPs (primarily endothelial and leukocyte MPs), which contribute to the initiation of atherosclerosis due to endothelial dysfunction by decreasing nitric oxide synthesis, have been reported to be significantly higher in ACS patients 39) and are considered to be a primary source of the blood-borne tissue factor involved in thrombus propagation at the site of vascular injury 38,40,41) .…”
Section: Role Of Tissue Factor and Microparticles In Thrombus Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…Microparticles (MPs) are 0.1-1-μm membrane vesicles that are released into the extracellular space following cell activation or apoptosis 33) . Several cardiovascular risk factors, such as oxidative stress and elevated levels of lipoproteins and cytokines, increase the release of MPs from vascular/circulation cells 34,35) , and a large number of studies have proposed that MPs may contribute to atherosclerotic plaque development and thrombus formation/progression [35][36][37][38] . In fact, circulating MPs (primarily endothelial and leukocyte MPs), which contribute to the initiation of atherosclerosis due to endothelial dysfunction by decreasing nitric oxide synthesis, have been reported to be significantly higher in ACS patients 39) and are considered to be a primary source of the blood-borne tissue factor involved in thrombus propagation at the site of vascular injury 38,40,41) .…”
Section: Role Of Tissue Factor and Microparticles In Thrombus Formationmentioning
confidence: 99%
“…At the time of plaque disruption, locally released tissue factor-positive and leukocyte-derived MPs play an important role in fibrin-rich thrombus formation [35][36][37][38][39][40][41][42] . Moreover, activated inflammatory cells, such as neutrophils, macrophages and eosinophils, contribute to the growth of a thrombus 17,89,90) .…”
Section: )mentioning
confidence: 99%
“…18 Circulating annexin V is a ligand for PS and inhibits the uptake of MPs into endothelial cells. 21 The level of circulating annexin V was not different before and after cardiac stress in patients with or without significant coronary stenosis ( Figure 3B), suggesting an annexin V-independent regulation of EMP uptake. In contrast, stimulation of target endothelial cells with sera collected from patients with coronary stenosis after cardiac stress augmented expression of endothelial PSR, a main regulator of EMP uptake ( Figure 3C).…”
Section: Endothelial Microparticle Uptakementioning
confidence: 86%
“…Early findings utilizing this approach seem to corroborate observations from genome-wide association studies as well as plaque compositional changes in plaque revealed by highresolution MRI Chai, personal communication. Circulating multivesicular bodies derived from platelets, monocytes, and red blood cells have also been characterized specifically with regard to the miRNA that they contain, and have been shown to have roles in VCAM1 inhibition, activation of plaque macrophages, and in cell-to-cell signalling 147 that are central to atherosclerosis progression 148 .…”
Section: Molecular Techniques-mentioning
confidence: 99%